Internet misuse or abuse at workplace a gross misconduct - Ali Mohamed, Ashgar Ali (Lexis Nexis Malaysia Sdn Bhd, 2018)
This article basically seeks to examine the misuse or abuse of the employer's internet facilities by an employee such as circulating emails that contained abusive language, profanity or assessing prohibited websites among others and its consequence with reference to the awards of the Industrial Court.